An Incidentally Detected 46,XY Disorder of Sex Development during Kinship Testing - Sojung Lim; Soong Deok Lee; Sohee Cho (Korean Journal of Legal Medicine, 2026)
In forensic short tandem repeat (STR) analysis, sex typing is routinely performed using markers such as amelogenin, Y-STRs, and Y-insertion/deletion polymorphisms (Y-InDels). Although autosomal STR markers are not intended to reveal health-related information, sex typing may incidentally reveal disorders of sex development (DSDs). Herein, we present the case of a 73-year-old woman in whom a 46,XY DSD was incidentally identified during kinship testing. Both AMELX and AMELY were detected with similar peak heights in STR analysis, along with the detection of Y-STR and Y-InDel markers. Furthermore, Y- and X-STR analyses showed complete Y-STR profiles and hemizygosity across all X-STR loci, suggesting an XY chromosomal constitution. The participant reported a history of primary amenorrhea, and 46,XY DSD was suspected. Targeted sequencing of 63 DSD-related genes revealed a splice donor site variant in the androgen receptor (AR) gene (c.2173+1G>A), suggesting androgen insensitivity syndrome. Although rare, discordance between chromosomal sex determined by DNA testing and phenotype may indicate an underlying DSD, and further diagnostic evaluation and medical intervention may be warranted. Referral to an appropriate medical professional may be necessary, although not the original purpose of testing. However, the disclosure of such incidental findings can raise ethical concerns, including privacy issues and should be communicated with caution. Finally, forensic professionals should be aware of the limitations of sex typing and its potential to be misleading in investigative contexts, where sex inferred from STR typing can lead to the exclusion of suspects.